Ecophysiological Responses of the Lesser Mealworm Alphitobius diaperinus Exposed to Desiccating Conditions - Engell Dahl, Julie; Renault, David (Frontiers in Physiology, 2022)
In order to improve predictions of the impacts of climate change on insects, this study aimed to uncover how exposure to dry conditions can affect the biology of the invasive pest beetle Alphitobius diaperinus in terms of longevity, activity, water content, metabolic profiles and fecundity. We measured desiccation resistance in adults of A. diaperinus by recording the time the beetles could survive desiccation stress. We found that the species was highly desiccation resistant, with about 50% of the insects exposed to desiccation being able to survive for 30 days, and some individuals even survived for up to 50 days at 14% ± 2 relative humidity. There was no evidence of active upregulation of sugars or other metabolites which the beetles could have used to better tolerate desiccation. Food deprivation affected both control (food deprivation, no desiccation) and treatment (food deprivation, desiccation) groups, as their metabolic phenotypes changed similarly after 1 week of treatment. Also, the activity of beetles from both control and desiccation treatments was similarly increased two weeks after the experiment had started. Even if there were no changes in the metabolic phenotypes of the insects experiencing desiccating conditions, beetles exposed to desiccation for eight days had a significantly reduced reproductive output as compared with control insects. This result indicated a physiological cost of drought resistance or repair of stress-incurred damages. The exact nature of that effect (e.g. direct or indirect physiological costs) has not yet been described for tenebrionid beetles, and should be investigated in future studies.